Premio Póster: Resolución endoscópica de quistes epidermoides del ángulo pontocerebeloso: Nuestra Experiencia. - Carrera, Casco; Feldman, Santiago; Guevara, María; Núñez, Maximiliano; Mural, Miguel; Salas, Eduardo (Revista Argentina de Neurocirugía, 2022)
Introduction: epidermoid cysts are benign tumors of ectodermal origin that constitute 1% of all intracranial tumors. Its most frequent location is the cerebellopontine angle (CPA), constituting the 3rd most frequent tumor in that anatomical region.Objective: to present our institutional case series of cerebellopontine angle epidermoid cysts treated endoscopically.Materials y methods: We performed a retrospective analysis of all patients who underwent whole course endoscopic resection of cerebellopontine angle epidermoid cysts in our institution during the period of time between 2017 and 2022. Demographic data, preoperative evaluation, intraoperative images and post-operative evolution were evaluated.Results:  Five patients were surgically treated with a pure endoscopic modality under intraoperative neurophysiologic monitoring, in park-bench position using a retrosigmoid approach. The mean age was 46 years (range 30-51); all of them were men; the most common symptom at presentation was ataxia followed by disfunction of V, VI and VII cranial nerve. We have no cases of aseptic meningitis. One patient presented with grade II facial palsy (H&B II) postoperative. In 4 cases the resection achieved was subtotal. Three patients improved the facial nerve palsy and cerebellar symptoms.Conclusion: The soft consistency and lack of blood supply of the epidermoid cysts, allows their endoscopic resection. The endoscope provides a panoramic view of the CPA and also increased maneuverability in such a narrow corridor. The dynamic retraction decreases the possibility of cerebellar injury. The main disadvantage of endoscopy is its long learning curve and the absence of 3D perception of the surgical field.
Keywords: epidermoid cysts; Endoscopy; Cerebellopontine Angle